A Review of Bioinformatics Tools for Bio-Prospecting from Metagenomic Sequence Data - Roumpeka, Despoina D.; Wallace, R. John; Escalettes, Frank; Fotheringham, Ian; Watson, Mick (Frontiers in Genetics, 2017)
The microbiome can be defined as the community of microorganisms that live in a particular environment. Metagenomics is the practice of sequencing DNA from the genomes of all organisms present in a particular sample, and has become a common method for the study of microbiome population structure and function. Increasingly, researchers are finding novel genes encoded within metagenomes, many of which may be of interest to the biotechnology and pharmaceutical industries. However, such "bioprospecting" requires a suite of sophisticated bioinformatics tools to make sense of the data. This review summarizes the most commonly used bioinformatics tools for the assembly and annotation of metagenomic sequence data with the aim of discovering novel genes.